2014
DOI: 10.1002/anie.201309135
|View full text |Cite
|
Sign up to set email alerts
|

Organelle‐Specific Activity‐Based Protein Profiling in Living Cells

Abstract: A multimodal acidic organelle targeting activity-based probe was developed to measure subcellular native enzymatic activity of cells by fluorescent microscopy and mass spectrometry. A cathepsin reactive warhead, conjugated to a weakly basic amine and a clickable alkyne, for subsequent appendage of a fluorophore or biotin reporter tag, accumulated in lysosomes as observed by Structured Illumination Microscopy (SIM) in J774 mouse macrophage cells. Analysis of in vivo labeled J774 by mass spectrometry showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
(30 reference statements)
0
30
0
Order By: Relevance
“…[30] In the current work, the interior localization of an amino-functionalized molecule in lysosomes in live cells is demonstrated. The application of two-color SIM on live HeLa (S3) cells transfected with Fusion-Red-LAMP and co-stained with compound 4 confirms that FusionRed-LAMP is anchored on the membrane of lysosomes, whereas compound 4 is confined in the lumen of lysosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] In the current work, the interior localization of an amino-functionalized molecule in lysosomes in live cells is demonstrated. The application of two-color SIM on live HeLa (S3) cells transfected with Fusion-Red-LAMP and co-stained with compound 4 confirms that FusionRed-LAMP is anchored on the membrane of lysosomes, whereas compound 4 is confined in the lumen of lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…[29] Wright and co-workers have recently shown that the weakly basic 3-(2,4-dinitroanilino)-3'-amino-N-methyldipropylamine (DAMP)-derived protein activity probes are encapsulated in lysosomes in fixed cells using SIM. [30] In the current work, the interior localization of an amino-functionalized molecule in lysosomes in live cells is demonstrated. The application of two-color SIM on live HeLa (S3) cells transfected with Fusion-Red-LAMP and co-stained with compound 4 confirms that Fu-sionRed-LAMP is anchored on the membrane of lysosomes, whereas compound 4 is confined in the lumen of lysosomes.…”
Section: Structured Illumination Microscopy (Sim)mentioning
confidence: 87%
“…[13][14][15][16][17] The peptidic part of such covalent modifiers accounts for sufficient affinity to be accommodated in the active site of the target protease due to specific non-covalent interactions mainly with the S1-S4 binding pockets. In particular, epoxide derivatives and acyloxymethyl ketones have been successfully devolved to activity-based probes for cysteine cathepsins.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 While relatively unexplored in an autophagy context compared with the methods outlined in previous sections, chemical proteomics techniques such as bio-orthogonal noncanonical amino acid tagging (BONCAT) and affinity-based protein profiling (ABPP) have already been successfully used for novel and pioneering studies in autophagy and will be further discussed in the corresponding section later in this review. [47][48][49][50]…”
Section: Chemical Proteomicsmentioning
confidence: 99%